Parametric study of a wave energy converter (Searaser) for Caspian Sea. (August 2018) - Babajani, Aliakbar; Jafari, Mohammad; Hafezisefat, Parinaz; Mirhosseini, Mojtaba; Rezania, Alireza; Rosendahl, Lasse
Abstract: Over the past decades, different types of energy converters have been invented because wave energy is a renewable energy source with high potential for extraction of considerable clean energy. Many numerical and experimental tests have been conducted to calculate the power generation of ocean waves, and these tests have demonstrated the significance of this energy. In this paper, the hydrodynamic performance of a new energy converter called "Searaser" has been evaluated using numerical simulation to study different aspects of this energy converter. Since previous studies have found ocean wave energy converters excellent for implementation in the Caspian Sea, the aim of this study is to investigate its performance for that sea, so this study presents a numerical simulation of Searaser inside an experimental wave tank using commercial software Flow-3D. To model the motion of the energy converter, Reynolds Averaged Navier-Stokes was coupled with a volume-of-fluid (VOF) model to generate three-dimensional numerical linear propagating waves for solving the fluid field. Grid independency was also carried out to determine the best mesh numbers for the original simulations. Finally, the Searaser hydrodynamic performance was numerically calculated for different wave heights, and some of the most important parameters of point absorbers were captured, including output flow rate in different seasons, extractable wave power, and output power. Accordingly, the obtained results indicate that the output flow rate and the power generation are significantly increased by incremental changes in wave height, and using this type of converter device has potential for practical and profitable use in industrial applications.